2023
DOI: 10.2174/1574888x16666210916145717
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mesenchymal Stem Cells in Crohn's Disease and Perianal Fistulas: A Narrative Review

Abstract: : Crohn's disease (CD) which usually leads to anal fistulas among patients is the most important inflammatory bowel disease that causes morbidity in many people around the world. This review article proposes using MSCs as a hopeful therapeutic strategy for CD and anal fistula treatment in both preclinical and clinical conditions. Finally, Darvadstrocel - a cell based medication to treat complex anal fistulas in adults- as the only European Medicines Agency (EMA)-approved product for the treatment of anal fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 182 publications
0
2
0
Order By: Relevance
“…To date, clinical trials have been conducted using MSCs as novel therapeutic agents to treat various diseases, including acute diseases, such as ischaemic stroke and myocardial infarction. MSCs are also intended anti-inflammatory therapy for diseases caused by uncontrolled inflammatory reactions, such as acute graft-versus-host disease (GvHD) and Crohn’s disease [ 329 , 330 , 331 , 332 ].…”
Section: Application Of Msc-derived Evs In Modulating the Immune Resp...mentioning
confidence: 99%
“…To date, clinical trials have been conducted using MSCs as novel therapeutic agents to treat various diseases, including acute diseases, such as ischaemic stroke and myocardial infarction. MSCs are also intended anti-inflammatory therapy for diseases caused by uncontrolled inflammatory reactions, such as acute graft-versus-host disease (GvHD) and Crohn’s disease [ 329 , 330 , 331 , 332 ].…”
Section: Application Of Msc-derived Evs In Modulating the Immune Resp...mentioning
confidence: 99%
“…Some studies on local injection of MSCs for treatment of anal fistula in CD have shown it is safe and effective, and a phase 3 clinical trial is under way. 10 , 11 , 12 Sophie Vieujean et also used local injection to treat CD patients with stenosis 13 and showed allogenic bone-marrow derived MSCs tropic injection in CD stricture was well tolerated and may offer a benefit. However, whether MSCs can alleviate or cure intestinal ulcers in CD has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, local injection of mesenchymal stem cells (MSCs) has shown notable promising results in the treatment of PFs[ 11 ]. MSCs are a heterogeneous subset of stromal stem cells.…”
Section: Introductionmentioning
confidence: 99%